Key Affecting Towards Financial Performance And Sustainability On Social Enterprises In Indonesia - Permana, Dudi (Indonesian Scientific Publication, 2024)
This study explores the complex relationships between social impact projects, marketability, sustainability, financial performance, and environmental conservation measures in Indonesian social enterprises. Data from 348 social enterprises were quantitatively collected, and structural equation modelling was used for analysis. Strong validity and reliability were demonstrated by the measurement model, and the model fit analysis validated the general fit of the model. The structural model showed strong positive correlations between social impact programmes, marketing prowess, financial performance, and environmental preservation and sustainability policies. To improve financial performance and overall sustainability, social enterprises should integrate sustainable practices into their fundamental strategies, as highlighted by these findings, which offer insightful information for practitioners, policymakers, and academics. This research provides tangible implications for social enterprises in improving financial performance so as to impact empowerment.